Method for analysing the risk of overuse injury in gymnastics - Beatty, K. T.; McIntosh, A. S.; Frechede, B. O. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The purpose of this study was to propose and assess a method for the evaluation of all loads experienced during gymnastics training. The method is based on the measurement of acceleration on the gymnast. Twelve gymnasts performed a range of gymnastics skills with an impact component. Ground reaction forces and acceleration at the pelvis were measured. There were significant correlations between peak GRF and peak acceleration during landing from gymnastics skills for individual participants. This testing showed the potential for this method to be applied in a study of injury risk factors outside the laboratory environment. At present, this relationship means that acceleration can be used as an estimation of force, after calibrating acceleration to ground reaction force for the individual.